Neonatal and Pediatric Candidemia: Results From Population-Based Active Laboratory Surveillance in Four US Locations, 2009–2015. (7th March 2018) - Benedict, Kaitlin; Roy, Monika; Kabbani, Sarah; Anderson, Evan J; Farley, Monica M; Harb, Sasha; Harrison, Lee H; Bonner, Lindsay; Wadu, Vijitha Lahanda; Marceaux, Kaytlyn; Hollick, Rosemary; Beldavs, Zintar G; et al.
Abstract: Introduction: Candida is a leading cause of healthcare-associated bloodstream infections in the United States. Infants and children have unique risk factors for candidemia, and the Candida species distribution in this group is different that among adults; however, candidemia epidemiology in this population has not been described recently. Methods: We conducted active population-based candidemia surveillance in 4 US metropolitan areas between 2009 and 2015. We calculated incidences among neonates (0–30 days old), infants (0–364 days old), and noninfant children (1–19 years old), documented their clinical features and antifungal drug resistance. Results: We identified 307 pediatric candidemia cases. Incidence trends varied according to site, but overall, the incidence in neonates decreased from 31.5 cases/100000 births in 2009 to 10.7 to 11.8 cases/100000 births between 2012 and 2015, the incidence in infants decreased from 52.1 cases/100000 in 2009 to 15.7 to 17.5 between 2012 and 2015, and the incidence in noninfant children decreased steadily from 1.8 cases/100000 in 2009 to 0.8 in 2014. Common underlying conditions were prematurity in neonates (78%), surgery in nonneonate infants (38%), and malignancy in noninfant children (28%). Most neonate cases were caused by C albicans (67%), whereas non- C. albicans species accounted for 60% of cases in nonneonate infants and noninfant children. Fluconazole and echinocandin resistance rates were low overall. Thirty-day crude mortality was 13%. Conclusions: The incidence of candidemia among neonates and infants declined after 2009 but remained stable from 2012 to 2015. Antifungal drug resistance is uncommon. Reasons for the lack of recent declines in neonatal and infant candidemia deserve further exploration. In this article, we describe the epidemiology of candidemia in children in the United States and on the basis of data collected as part of US Centers for Disease Control and Prevention active population-based surveillance. Trends in incidence, clinical characteristics, species distribution, and resistance rates are presented.